Rheological Behavior of Carbon Nanotubes as an Additive on Lithium Grease - Alaa Mohamed; Aly Ahmed Khattab; Tarek Abdel Sadek Osman; Mostafa Zaki (Journal of Nanotechnology)
The rheological behaviors of carbon nanotubes (CNTs) as an additive on lithium grease at different concentrations were examined under various settings of shear rate, shear stress, and apparent viscosity. The results indicated that the optimum content of the CNTs was 2%. These experimental investigations were evaluated with a Brookfield Programmable Rheometer DV-III ULTRA. The results indicated that the shear, stress and apparent viscosity increase with the increase of CNTs concentration. The microstructure of CNTs and lithium grease was examined by high resolution transmission electron microscope (HRTEM) and scanning electron microscope (SEM). The results indicated that the microscopic structure of the lithium grease presents a more regular and homogeneous network structure, with long fibers, which confirms the rheological stability.